2013
DOI: 10.1186/gb-2013-14-12-r140
|View full text |Cite
|
Sign up to set email alerts
|

Spatial expression of transcription factors in Drosophilaembryonic organ development

Abstract: BackgroundSite-specific transcription factors (TFs) bind DNA regulatory elements to control expression of target genes, forming the core of gene regulatory networks. Despite decades of research, most studies focus on only a small number of TFs and the roles of many remain unknown.ResultsWe present a systematic characterization of spatiotemporal gene expression patterns for all known or predicted Drosophila TFs throughout embryogenesis, the first such comprehensive study for any metazoan animal. We generated RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
157
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(165 citation statements)
references
References 55 publications
6
157
1
1
Order By: Relevance
“…For one of these genes, hgo, we further confirmed this Grh-mediated expression in vivo by assaying expression of a lacZ transgene driven by either the wild-type hgo promoter or one harboring mutations in the identified Grh-binding site ( Figure 5C). The expression pattern of lacZ driven by the wild-type hgo promoter resembles expression of the endogenous gene as reported by the Berkeley Drosophila Genome Project (Tomancak et al 2002(Tomancak et al , 2007Hammonds et al 2013). Mutations in the single canonical Grh-binding motif result in background levels of staining ( Figure 5C).…”
Section: Grh-binding Sites Are Largely Invariant Over Developmentsupporting
confidence: 63%
“…For one of these genes, hgo, we further confirmed this Grh-mediated expression in vivo by assaying expression of a lacZ transgene driven by either the wild-type hgo promoter or one harboring mutations in the identified Grh-binding site ( Figure 5C). The expression pattern of lacZ driven by the wild-type hgo promoter resembles expression of the endogenous gene as reported by the Berkeley Drosophila Genome Project (Tomancak et al 2002(Tomancak et al , 2007Hammonds et al 2013). Mutations in the single canonical Grh-binding motif result in background levels of staining ( Figure 5C).…”
Section: Grh-binding Sites Are Largely Invariant Over Developmentsupporting
confidence: 63%
“…One potential explanation for this could be that more miRNAs than TFs are expressed in highly restricted manner. Indeed, although it looks like a large fraction of miRNAs could fall into this 'highly restricted' category, a systematic study in Drosophila embryos shows that out of ∌700 TFs only 20% show 'single-organ specificity', and the majority are expressed across multiple organ systems (Hammonds et al, 2013). However, more systematic expression analyses allowing comparisons within species are needed to address this issue further.…”
Section: Discussionmentioning
confidence: 99%
“…A target gene was assigned to DV enhancers only if the enhancer's expression domain overlapped and resembled the gene's expression domain (Supplemental Material). For this purpose, published mRNA in situ hybridization data from the Berkeley Drosophila Genome Project (BDGP) (Tomancak et al 2002(Tomancak et al , 2007Hammonds et al 2013) database were used for enhancers identified by Kvon et al (2012) and Ozdemir et al (2011). For some of these enhancers, no target gene was identified with confidence, and thus those enhancers were not included in mRNA-seq analysis shown in Supplemental Figure S1 (Supplemental Material).…”
Section: List Of Known DV Enhancersmentioning
confidence: 99%